Demographic study of the population of dogs and cats domiciled in the southeastern sector of Bucaramanga, Colombia - Florez Muñoz, Angel Alberto (2019)
The aim of this investigation was to determine the demographic characteristics of the population of dogs and cats domiciled in the southeaster sector of Bucaramanga, department of Santander (Colombia) in 2016-2017. A descriptive cross-sectional study was carried out. A survey was conducted to pet owners to get information on the species, breed, sex, age, animal vaccinated and dewormed, type of feeding and reason for pet ownership. Results showed that 97.1% of the homes had dogs or cats as pets. The average of dogs and cats per dwelling was 0.67 (227 dogs / 339 dwellings) and 0.30 (102 cats / 339 dwellings), respectively. The person: dog and person: cat ratio was 4.33 and 9.64, respectively. The main reason for the tenure of dogs or cats was the affective (92.1 and 98%, respectively). Furthermore, there was a predominance of male pets over females.